(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was carried out in the farmers field at the MLT site Tularampur, Narail (AEZ-11) during the rabi season of 2011-12 to evaluate the performance of newly released mustard varieties to Zn fertilization. Three levels of zinc 2, 3 and 4 kg/ha from zinc sulphate was used in BARI Sharisha-14. The experiment was carried out in a tree with 6 dispersed replications. Response of mustard to zinc fertilizer was significantly evident for yield. The highest yield (1.42 t/ha) was obtained from T1(3 kg Zn/ha) which was statistically higher than T2 (4 kg Zn/ha) yielding 1.37 t/ha. Both the treatments gave higher yields over the control. From the economic analysis, the highest gross margin was observed (Tk. 47695/ha and Tk. 44595/ha) and highest benefit cost ratio (BCR) (1.57 and 1.45) obtained from T2 treatment followed by T3 treatment, respectively. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22037 J. Environ. Sci. & Natural Resources, 6(1): 37-40 2013